Alternative therapies for recurrent cystitis in menopausal women - E. V. Kulchavenya; L. S. Treyvish; E. V. Telina (Медицинский совет, 2022)
Worldwide, urinary tract infections (UTIs) are reported in 150-250 million people per year. Annual direct and indirect costs of UTIs for overall patients are estimated to be from $2.4 billion to $3.5 billion Uropathogenic Escherichia coli is the most common cause of UTIs. These bacteria have the ability to colonize urothelium, persist in epithelial cells, and form quiescent biofilms. This bacterial reservoir may provide a source for bacterial persistence and UTIs recurrence. Besides, recurrent UTIs may be caused by the translocation of other bacteria which originate from the gastrointestinal tract or reinfections due to external sources. Menopause and pregnancy are considered as complicating factors that predispose to UTIs. Oral vaccine OM-89 and D-mannose are specified in the European Urological Association guidelines among non-pharmacological methods for the prevention of recurrent UTIs in postmenopausal women. The rationale to the use of D-mannose in UTI prophylaxis is based on its competitive inhibition of bacterial adherence to urothelial cells due to binding of type 1 fimbriae expressed on the bacteria. Exogenous D-mannose is absorbed, but not metabolized by the human body and it is excreted intact in urine. In vivo and in vitro studies showed the ability of mannose-like molecules to provide a 2-fold reduction of bacterial load in the urinary tract after 4 intravesical instillations. Clinical studies also demonstrated a high efficacy of the six months course of oral mannose in the prevention of UTIs.